2020
DOI: 10.1097/pep.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vestibular/Ocular-Motor Screen Scores in Adolescents Treated With Vestibular Therapy After Concussion

Abstract: Purpose: To examine interrelationships among Vestibular/Ocular-Motor Screen (VOMS) items and to characterize the recovery of VOMS performance in a sample of adolescents treated with vestibular physical therapy (VPT) after concussion. Methods: Seventy-seven patients with concussion and 77 participants without concussion completed the study. Adolescents with concussion received an individualized VPT intervention consisting of targeted exercises for gaze s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…VOMs can capture improvements over the course of vestibular physical therapy (VPT) when administered at initiation and termination of treatment. It should be noted that participants may still experience positive VOMS scores at the conclusion of therapy, however, these scores are often comparable to scores observed in a sample of adolescents without concussion (Alsalaheen et al, 2020).…”
Section: Vestibular Rehabilitationmentioning
confidence: 76%
“…VOMs can capture improvements over the course of vestibular physical therapy (VPT) when administered at initiation and termination of treatment. It should be noted that participants may still experience positive VOMS scores at the conclusion of therapy, however, these scores are often comparable to scores observed in a sample of adolescents without concussion (Alsalaheen et al, 2020).…”
Section: Vestibular Rehabilitationmentioning
confidence: 76%
“…Previous studies assessing both in-office and athome vestibular rehabilitation programs in pediatric patients have demonstrated improvements in visio-vestibular function (18, 19, 22). Alsalaheen et al (19) found that in-office vestibular therapy supplemented with home exercises significantly improved all elements of the Vestibular/Oculomotor Screening (VOMS) assessment. Our results more closely align with a previous study assessing an at-home program only, which found that a 4-week (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Visual and vestibular impairments are estimated to occur in up to 88% of adolescent concussion patients (15)(16)(17) and have been associated with prolonged recovery (17). In-office therapy targeting vision and vestibular function has demonstrated improved clinical outcomes, including overall symptom reduction (18), improved vestibulo/ocular-motor performance (19), and earlier medical clearance (20) in adults and adolescents. Additionally, early initiation (≤30 days) of vestibular physical therapy has been associated with earlier return-to-play and symptom resolution in pediatric and young adult patients (aged 5-23 years) (21).…”
Section: Introductionmentioning
confidence: 99%
“…This scoring method is consistent with the scoring method in the original VOMS investigation, 3 as well as subsequent investigations examining various aspects related to VOMS. 11,26 In addition to a symptom score, the NPC distance was measured from the point at which the participant reported diplopia on a target moving slowly toward their face. A tongue depressor with a 14-point font "X" at the tip was used as the target.…”
Section: Vestibular/ocular Motor Screeningmentioning
confidence: 99%